The impact of transformational and transactional leadership styles on organizational innovativeness - Dukanac Milica; Stojanović-Aleksić Vesna; Zlatanović Dejana (Anali Ekonomskog fakulteta u Subotici, 2025)
Transformational leadership fosters organizational innovativeness by inspiring and motivating employees to challenge the status quo, embrace change, and generate creative solutions. The study aims to demonstrate the effects of transformational and transactional leadership on organizational innovativeness, particularly in the context of companies operating in the Republic of Serbia. The research was conducted among 202 employees in the Republic of Serbia. To ensure internal consistency, reliability analysis was employed, while multiple regression analysis was utilized to assess the influence of the independent variables on the dependent variable. The findings indicate that transformational leadership has a statistically significant positive effect on organizational innovativeness. Conversely, no statistically significant effect of transactional leadership on organizational innovativeness was observed. Future research models could explore the impact of individual dimensions of transformational and transactional leadership on organizational innovativeness. Additionally, it is recommended to investigate the relationship between these leadership styles and organizational innovativeness across different countries. The practical implications suggest that leaders should adopt transformational leadership to enhance organizational innovativeness and promote employee creativity. To the authors' knowledge, no existing studies in the domestic literature have comprehensively examined the effects of both transformational and transactional leadership on organizational innovativeness.